LEGAL REVOLUTIONARIES AT YALE IN A TIME OF POLITICAL AND SOCIAL CHANGE - Garth, Bryant G. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
My comment on the fascinating personal accounts of experiences with the Yale Law and Modernization program will be in part personal. My own career and research interests are part of the ripple effect of that program and of the scholars who participated in it. After offering that personal account, I will try to look at the context for the Law and Modernization initiative in relation to the changing role of law and lawyers in the US and the way in which that role was exported as part of Cold War strategies. I will suggest that the battles around the Law and Modernization Program provide strong evidence of the crisis during an era of relative idealism (not inconsistent with US hegemonic designs abroad and social control policies at home) connected to modernization and what Trubek and Galanter termed liberal legalism.<a title="" href="https://d.docs.live.net/a4fa3b7694794c6e/REVISTA%20ESTUDOS%20INSTITUCIONAIS/Vol7%20Num2/Artigos%20Internacionais/7.%20Legal%20Revolutionaries%20at%20Yale%20in%20a%20Time%20of%20Political%20and%20Social%20Change%20(Garth).docx#_ftn1">[1] What’s more, the program nurtured leaders in producing scholarship designed to update or replace liberal legalism, legal missionaries, and legal imperialism. Much of what we know as Law and Society, Critical Legal Studies, and other critical approaches came from these scholars and the events around Law and Modernization. I was a freshman undergraduate at Yale at the time of the beginnings of the Law and Modernization program in the Law School in 1968, although I had no sense of the program then. My undergraduate experience was all about the left, the critique of pluralism, European critical theory, and US critical histories. I told my historian advisor that I was thinking of law school (after he told me there were no positions in history), and he warned me about the conservatism, telling me among other things that law faculty tended to drive American cars. When there were demonstrations and strikes around the Bobby Seale trial in New Haven in 1970, followed by the demonstrations and strikes against the Cambodian invasion, I remember a forum where a law student said they could not strike because of the importance of their legal education for solving social problems. In retrospect, there was a sense among non-law students and activists, I think, that elite law was not very relevant to what was going on outside.<a title="" href="https://d.docs.live.net/a4fa3b7694794c6e/REVISTA%20ESTUDOS%20INSTITUCIONAIS/Vol7%20Num2/Artigos%20Internacionais/7.%20Legal%20Revolutionaries%20at%20Yale%20in%20a%20Time%20of%20Political%20and%20Social%20Change%20(Garth).docx#_ftn2">[2] From the perspective of those within the law school, however, the accounts of the Law and Modernization cohort suggest that the students were nevertheless way in front of the general faculty.